2015
DOI: 10.1111/1744-7917.12273
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the interaction types of two Bt toxins Cry1Ac and Cry2Ab on suppressing the cotton bollworm by using multi‐exponential equations

Abstract: Transgenic crops are increasingly promoted for their practical effects on suppressing certain insect pests, but all transgenic crops are not equally successful. The insect pests can easily develop resistance against single Bacillus thuringiensis (Bt) toxin transgenic crops. Therefore, transgenic crops including two or more mixed Bt-toxins can solve this problem by delaying the resistance development and killing the majority of targeted pests before the evolution of resistance. It is important to test the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, in China, the Bt cotton is only from a single Bt toxin strain and cotton bollworms are easy to develop the resistance to such a single toxin. A better strategy is to use other transgenic cotton with multiple Bt toxin combination (Shi et al 2015). However, even though using the effective bi-toxin cotton, it is still impossible to kill all cotton bollworms in the field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in China, the Bt cotton is only from a single Bt toxin strain and cotton bollworms are easy to develop the resistance to such a single toxin. A better strategy is to use other transgenic cotton with multiple Bt toxin combination (Shi et al 2015). However, even though using the effective bi-toxin cotton, it is still impossible to kill all cotton bollworms in the field.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lu et al (2010) reported that outbreaks of mirid bugs (Heteroptera: Miridae) in Bt cotton fields have become more frequent, and the species is now a dominant insect pest of the cotton crop. While transgenic cotton can kill the majority of cotton bollworms that are initially sensitive to Bt toxins (Roush 1998;Wei et al 2014;Shi et al 2015), the evolution of resistance to Bt toxins in pests will gradually weaken the effects of Bt cotton (Tabashnik 1994). This interaction between transgenic crops and climate change on the population dynamics of insect pests merits further investigation.…”
Section: Discussionmentioning
confidence: 99%